Teaching and learning about dementia in UK medical schools: a national survey - Tullo, Ellen, StClair; Gordon, Adam L. (BioMed Central Ltd, 2013)
Background: Dementia is an increasingly common condition and all doctors, in both primary and secondary care environments, must be prepared to competently manage patients with this condition. It is unclear whether medical education about dementia is currently fit for purpose. This project surveys and evaluates the nature of teaching and learning about dementia for medical students in the UK.